Typology-Based Counter-Terrorism Prevention Implementation in Bima City: A Soft Systems Methodology Approach and the SAKTI MARA Model, West Nusa Tenggara Province - Bangbang Surono; Muchlis Hamdi; Dahyar Daraba; Kusworo Kusworo; Muhammad Unggul Abdul Fattah (Sekolah Tinggi Agama Islam Kuningan, 2026)
policies that were adaptive, evidence-oriented, and institutionally sustainable, particularly in localities characterized by social vulnerability and latent network dynamics. Yet, empirically tested cross-ministerial implementation models at the sub-national level with explicit evaluation criteria remained understudied. Objective: This study examined the implementation of terrorism prevention through the Inter-Ministerial/Agency Synergy Programme in Bima City, West Nusa Tenggara, which had been designated as a vulnerability-based priority locus. The study analyzed the determinants associated with suboptimal implementation and formulated a context-sensitive implementation model. Methods: A descriptive qualitative design was employed. Data were collected through in-depth interviews, focus group discussions, field observation, and document review, and were validated through methodological triangulation. The analysis integrated implementation determinants policy substance, implementer behavior, network interaction, target-group participation, and resources—using Soft Systems Methodology (SSM) to translate the diagnostic findings into feasible improvements. Results: The findings indicated that interventions had remained generic; success standards and performance indicators had not been differentiated by target typology; network coordination had been weak and partially siloed; participation had varied across groups and perceived benefits; and resource and data governance had not yet supported evidence-based evaluation. Based on the SSM stages, the study formulated the SAKTI MARA model (Synergy between Ministries/Agencies Based on Radical Community Typology) to strengthen targeting, indicator design, and stratified resource allocation for local-level program implementation. Conclusion: The SAKTI MARA model provides a context-sensitive and adaptive implementation framework for strengthening typology-differentiated counter-terrorism prevention at the local level.